Kungliga Akademien för de fria konsterna: Om konst, makt och symbolisk ekonomi - Galli, Raoul (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
This article is based on fieldwork in a house. It discusses how different forms of capital are being transformed in direct or indirect connection to activities of The Royal Swedish Academy of Fine Arts, some of its members, and some of their social relations. Capital accumulation and transformation in predominantly symbolic economies, such as the field of art production, are normally long-term projects and therefore difficult to grasp through ethnographic observations. Here, the starting point is precisely a set of observations made of different artistic enterprises taking place in and around the Academy’s building in central Stockholm. Through the analysis of them an understanding is reached of how financial capital is transformed into field specific capital and, for example, the concept of "brand" is socially used to both explain and somewhat mask the economically interested nature of these enterprises on behalf of sponsors, investors, and producers in the art field.